Human PrimPol is a highly error-prone polymerase regulated by single-stranded DNA binding proteins - Guilliam, Thomas A. (Nucleic Acids Res, 2015)
PrimPol is a recently identified polymerase involved in eukaryotic DNA damage tolerance, employed in both re-priming and translesion synthesis mechanisms to bypass nuclear and mitochondrial DNA lesions. In this report, we investigate how the enzymatic activities of human PrimPol are regulated. We show that, unlike other TLS polymerases, PrimPol is not stimulated by PCNA and does not interact with it in vivo. We identify that PrimPol interacts with both of the major single-strand binding proteins, RPA and mtSSB in vivo. Using NMR spectroscopy, we characterize the domains responsible for the PrimPol-RPA interaction, revealing that PrimPol binds directly to the N-terminal domain of RPA70. In contrast to the established role of SSBs in stimulating replicative polymerases, we find that SSBs significantly limit the primase and polymerase activities of PrimPol. To identify the requirement for this regulation, we employed two forward mutation assays to characterize PrimPol's replication fidelity. We find that PrimPol is a mutagenic polymerase, with a unique error specificity that is highly biased towards insertion-deletion errors. Given the error-prone disposition of PrimPol, we propose a mechanism whereby SSBs greatly restrict the contribution of this enzyme to DNA replication at stalled forks, thus reducing the mutagenic potential of PrimPol during genome replication.